The effects of ergot alkaloids on the breeding stallion reproductive system. (December 2013) - Fayrer‐Hosken, R. A.; Hill, N. S.; Heusner, G. L.; Traylor‐Wiggins, W.; Turner, K.
Summary: Reasons for performing study: Ergot alkaloids cause a range of pathological conditions in mares. There is no evaluation of the effects of ergot alkaloids from endophyte‐infected tall fescue on the stallion breeding soundness examination spermiogram. Objectives: The objective of this study was to investigate the effect of ergot alkaloids from endophyte‐infected tall fescue on the stallion's reproductive functions. Study design: Crossover toxicology experiment. Methods: Six stallions were fed either toxic endophyte‐infected tall fescue seed or a nontoxic endophyte tall fescue seed (Flecha AR‐542, MaxQ). The fescue seed content was compounded at 45% of a grain diet and the stallions were fed the grain diet at 1% of their body weight. The stallions were fed the diet for 70 days, then rested for at least 70 days (no fescue seed) and then fed fescue seed for a second 70 days. At regular intervals blood sampling and a breeding soundness examination were performed. Results: The mean time to maximal systemic toxicity was 8.33 h after starting toxic seed ingestion with a mean toxicity level of 49.98 ng alkaloid/mg creatinine. After cessation of feeding toxic seed, the systemic alkaloid concentration fell to control levels within 48 h. There were no significant changes in sperm motility, sperm concentration, sperm cell morphology, total number of sperm cells, number of breeding doses, testicular volume, baseline and human chorionic gonadotropin stimulated testosterone levels. There were no changes in core body temperature and superficial scrotal temperature. The ejaculate from stallions consuming endophyte‐infected tall fescue seed had significantly lower gel‐free volume (47.5 ± 4.1 ml) than stallions consuming nontoxic endophyte tall fescue seed (62.8 + 4.3 ml, P<0.01). Conclusion: Ergot alkaloids decreased the gel‐free volume of stallions consuming high levels of ergot alkaloids but statistically significant effects on the spermiogram of adult breeding stallions were not found.